(untitled) (Conferencea, 2023)
The article is devoted to the problem of narratology in linguistics, in particular, to the scientific thoughts of M.M. Bakhtin on this problem. The article says that M.M. Bakhtin did not use the term "narratology" in his works, but at the same time this issue was not alien to him. It is also mentioned that the main thing in the scientific heritage of M.M. Bakhtin is that it develops its own theory of the novel genre as the historical poetics of the novel.